Preparation and humidity control performance of aluminum containing mesoporous molecular sieve synthesis from liquid crystal display waste glass and sandblasting waste. (March 2023) - Lin, Ya-Wen; Lee, Wei-Hao; Chen, Chiao-Ying; Lin, Kae-Long; Liu, Yan-Jun; Zhang, Wei-Qing; Lin, Mei-Yu
Abstract: This study developed a simple approach to synthesizing mesoporous molecular sieves (MMSs) using waste from sandblasting and the manufacture of liquid crystal displays. We developed a novel hydrothermal method used in conjunction with alkali fusion) to manufacture MMS humidity control material. XRD patterns revealed the index peak of the P6mm space group, which appeared as a high-order two-dimensional hexagonal arrangement of mesopores. The MMSs presented uniform pores ranging in size from 3.41 nm to 3.94 nm with the hexagonal structure typical of ordered MCM-41. These results indicate that synthesis at a higher temperature had a negligible effect on the structure of MMS in terms of band shift or attenuation. The higher water vapor adsorption/desorption capability of the resulting MMS (186.67 g/m 2 ) makes it an ideal humidity control construction material as an alternative to mechanical dehumidifiers, which are expensive and consume large quantities of energy. Graphical Abstract: ga1 Highlights: MMS containing Al is synthesized by alkali fusion and hydrothermal. The synthesized material had a high specific surface area of 1013 m 2 /g. The environmental humidity control and high performance of the material were observed. Determined the effective synthesis of MCM-41 mesoporous material from industrial waste.